The Effectiveness of Crowdfunding Promotions on Social Media in Affecting Donation Intention: An Exploratory Survey on Millennials - Gladys Greselda Gosal; Irantha Hendrika Kenang; Laura Mahendratta Tjahjono (Bina Nusantara University, 2022)
Social media has become an effective marketing tool, including donation-based crowdfunding platforms, to reach potential donors. The research aimed to analyze the effectiveness of social media promotion in affecting the online donation intention of millennial generations. With the S-O-R theory, the research used variables like content likeability (S), social media attributes (S), social media engagement (O), perceived credibility (O), and intention to donate (R). Then, quantitative measures were used by distributing questionnaires to the selected sample, and 152 responses were collected. The data were analyzed using SEM. The results show that intention to donate is indeed affected by social media engagement and perceived credibility. On the other hand, perceived credibility is affected by both content likeability and social media attributes. However, the results find that social media engagement is only affected by content likeability and is not influenced by social media attributes. The distinctive finding can be due to the different behavior shown by social media users toward fundraising platforms, as they only want to donate and rarely engage in the fundraiser’s social media. The research calls for further investigation using multidimensional constructs to evaluate the drivers of intention to donate. Alternatively, further research can also be conducted to analyze the behavioral differences between millennials and other generations.